Development of the optimal composition of tablets with the active substance potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate. Message 1. Study of the effect of auxiliary substances on bulk density, bulk density after shrinkage, fluidity and angle of natural slope of powder masses - R. O. Shcherbyna; O. V. Khromylova; H. R. Nimenko; V. O. Salionov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2024)
The pharmaceutical industry continually evolves to meet the demands of modern society for high-quality medications. One avenue of this advancement involves exploring new technologies for manufacturing tablet formulations that adhere to contemporary quality standards. An integral aspect of this process is the careful selection of optimal excipients that preserve the pharmacological activity of the active substance to the greatest extent possible. Investigating the impact of various excipients on the tablet compression process is pivotal to addressing this challenge. Therefore, the study of the influence of excipients on the pharmaco-technological properties of tablets with potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate is an important aspect, so as this substance has pronounced hepatoprotective and antioxidant properties.